On Structural Characterization and Computation of the Diameter and Girth of Bipartite Gap Poset Graphs with Python Application - Mehtab, Maria; Binyamin, Muhammad Ahsan; Asghar, Syed Sheraz; Alali, Amal S.; Mehmood, Khawar (Axioms, 2025)
In this article, a correspondence between some important classes of numerical semigroups and well-known families of bipartite graphs has been established. Also, it has been demonstrated that, if m(S) is the multiplicity of a numerical semigroup S, then the diameter and the girth of bipartite gap poset graphs are bounded by the numbers 2m(S)−3 and m(S)−1, respectively. Moreover, the Python code to compute the diameter and girth of gap poset graphs has been implemented.